John Ciardi papers in the Charles E. Feinberg collection - Feinberg, Charles E., 1899-1988; Ciardi, John, 1916-1986; Ciardi, John, 1916-1986.; Charles E. Feinberg Collection (Library of Congress)
Manuscripts of poems and prose, typescripts, notebooks, printed material, and other papers of author and poet John Ciardi. The largest portion of the collection consists of the printer's copy of Mid-Century American Poets (1950), edited by Ciardi, along with correspondence of major American poets associated with its production.
Library of Congress Rare Book and Special Collections Division.
Finding aid available in the Library of Congress Manuscript Reading Room.
Collection material in English.
Keywords: American poetry; Poets, American; Poets, American -- 20th century -- Correspondence; Collectors